Expressão plasmática e placentária da pentraxina 3 e do fator de crescimento de fibroblasto 2 na pré-eclâmpsia - Flávia Ivair Santiago de Oliveira (2020)
Preeclampsia (PE) is a systemic multifactorial disease that occurs from the twentieth week of gestation in previously normotensive women. It is characterized by arterial hypertension accompanied by one or more of the following conditions: proteinuria, thrombocytopenia, renal failure, impaired liver function, pulmonary edema and neurological symptoms. The imbalance between pro and antiangiogenic factors has been considered fundamental for the development of PE. Fibroblast Growth Factor 2 (FGF2) is one of the molecules expressed by the villi of the trophoblast and responsible for regulating the angiogenic process in physiological and pathological conditions. The highly specific interaction of FGF2 with the acute phase protein Pentraxin 3 (PTX3) prevents the engagement of FGF2 to its specific receptors and impair the biological activities FGF2-dependent, including angiogenesis. Some studies report the increased levels of PTX3 and FGF2 in plasma and sera of pregnant women that developed PE. However, it is not clear the involvement of these molecules and the impact of their interaction on the characteristic antiangiogenic state of the disease. Considering that the pathophysiological mechanisms that lead to the development of PE are still unclear, the importance of angiogenesis in the progression of PE, the pro-angiogenic action of FGF2 and its inhibition by PTX3, it is relevant to study the correlation between PTX3 and FGF2 in the context of PE. The aim of this study was to evaluate the plasma and placental concentration of PTX3 and FGF2 in normotensive and pre-eclamptic pregnant women, to correlate these levels with each other and with the clinical aspects of the disease. This is a case-control study that used 19 samples from non-pregnant women, 42 from normotensive pregnant women and 43 from pregnant women with PE. We detected by sandwich ELISA that the concentrations of PTX3 and FGF2 in the plasma of pregnant women with PE at the final third trimester of pregnancy are significantly higher (p <0.05) than those present in the plasma of normotensive pregnant women in the same period of gestation. The higher levels of PTX3 in the plasma of pregnant women with PE do not allow the discrimination between early and late PE. On the other hand, the concentration of FGF2 in the plasma of pregnant women who developed early PE was on average 2 times higher (37.45 pg / mL) than those observed in both the plasma of normotensive (15.77 pg / mL, p=0.002) and pregnant women with late PE (13.08 pg / mL, p=0.004). PTX3 and FGF2 behave independently and no correlation was found between the plasma concentration of these factors and neither with other risk factors for PE analyzed, such as primigestation and weight gain during pregnancy. However, the concentration of PTX3 has shown a positive correlation with that of ANX1A, an important pro-resolving molecule of inflammation. Our findings together corroborate, in Brazilian women, data from other authors that point out the increased concentration of PTX3 and FGF2 in PE. Our data show, in an unprecedented way, the plasma levels increase of FGF2 in early PE and the correlation between the concentration of PTX3 and ANX1A in the plasma of pregnant women with PE. The results presented here serve as a basis for carrying out other studies seeking to evaluate the predictive potential of FGF2 and PTX3 and to elucidate the biological role of these molecules in PE.